Copper-catalyzed aerobic oxidative decarboxylative amination of arylacetic acids: a facile access to 2-arylquinazolines. Issue 42 (13th April 2016) - Yan, Yizhe; Shi, Miaomiao; Niu, Bin; Meng, Xiangping; Zhu, Changrui; Liu, Gengyao; Chen, Ting; Liu, Yanqi
Abstract : An efficient copper-catalyzed oxidative decarboxylative amination of arylacetic acids with 2-aminobenzoketones and ammonium acetate under an oxygen atmosphere was first developed. Abstract : An efficient copper-catalyzed oxidative decarboxylative amination of arylacetic acids with 2-aminobenzoketones and ammonium acetate under an oxygen atmosphere was first developed. This reaction represents a novel avenue for 2-arylquinazolines in good to excellent yields via multiple C–N bond formations. This protocol features inexpensive copper as the catalyst, molecular oxygen as the sole oxidant, H2 O and CO2 as wastes, and a broad substrate scope.